High gain L-band erbium-doped fiber amplifier with two-stage double-pass configuration - Harun, Sulaiman Wadi; Tamchek, Nizam; Poopalan, Prabakaran; Ahmad, Harith (Indian Academy of Sciences, 2003)
An experiment on gain enhancement in the long wavelength band erbium-doped fiber amplifier (L-band EDFA) is demonstrated using dual forward pumping scheme in double-pass system. Compared to a single-stage single-pass scheme, the small signal gain for 1580 nm signal can be improved by 13.5 dB. However, a noise figure penalty of 2.9 dB was obtained due to the backward C-bund ASE from second stage and the already amplified signal from the first pass that extracting energy from the forward C-band ASE. The maximum gain improvement of 13.7 dB was obtained at a signal wavelength of 1588 nm while signal and total pump powers were fixed at -30 dBm and 92 mW, respectively.